An exploration of the fruit and vegetable "foodscape" in a university setting for staff: A preliminary study. Issue 1 (5th January 2015) - Bevan, Ann Lesley; Hartwell, Heather; Hemingway, Ann; Proença, Rossana Pacheco da Costa
Abstract : Purpose: – The potential for the foodservice industry to be part of a public health strategy has led to a new understanding of this sector's role in a wider interdisciplinary health environment. The purpose of this paper is to evaluate the influence of the foodscape on fruit and vegetable choice by staff in a higher educational setting. Design/methodology/approach: – Foodscape mapping of fruit and vegetable provision on campus was conducted to provide context. Two focus groups with staff and two interviews with foodservice managers took place to gain depth of understanding. Thematic analysis was conducted to allow for pattern and meaning to emerge. Findings: – Results demonstrate two main overarching themes; personal influence and food operator influence that impact on fruit and vegetable choice. In addition connectivity, perceptions of freshness, food quality and display seemed to be strong categories emerging from the data. Interestingly, this research indicated that consumers were more likely to eat fruit and vegetables when part of a composite dish than if served separately. Practical implications: – Providing a positive foodscape to enhance availability of fruit and vegetables may be challenging but helpful towards health promotion. Nevertheless, no "nudging" can control choice made by individuals, responsibility for healthy selection must always remain personal. Originality/value: – Knowledge gained by this pilot study will add to the body of literature and evidence base for further research while contributing to foodservice strategies which may promote increased fruit and vegetable consumption.